(untitled) (Research, Society and Development, 2022)
Objective: to demonstrate how adolescent care occurred in a reference unit in primary health care during the COVID-19 pandemic. Method: this is a qualitative and descriptive study, developed with professionals working in a health unit of the Acre. Data collection took place in May 2021, through a semi-structured interview. Data were analyzed following Bardin content analysis proposal. Results: during the pandemic, the service aimed at adolescents continued to occur normally, but individually, because due to restrictions imposed by the pandemic period collective actions aimed at this target audience were suspended. Among the activities offered, the main reasons for seeking care were medical and prenatal consultations and the search for vaccines and contraceptive methods. There was a decrease in the frequency of adolescents at the service and strategies were not designed to improve adherence, as the team’s efforts were concentrated to meet spontaneous demand, in order to mitigate the impacts caused by the pandemic. Conclusion: the service aimed at adolescents continued to occur during the pandemic, but according to spontaneous demand, which led to a decrease in access to the actions offered.